Pembelajaran Musik Tradisional (Pupuik Sarunai) Siswa Kelas X SMA Negeri 2 Hiliran Gumanti - Marlis Putri Nandina; Marzam Marzam (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
This study aims to know and describe the learning of traditional music (Pupuik Sarunai) of grade X students of SMA Negeri 2 Hiliran Gumanti. The type of research used in this study is qualitative research with a descriptive approach. The data in this study used primary data and secondary data. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data collection techniques include observation, literature study, interview and documentation study. The steps of analyzing data are data collection, data reduction, data display, verification and affirmation of conclusions. The results showed that the implementation of learning activities that were not in accordance with the module had an impact on the assessment of the learning outcomes of these students. From the evaluation of learning conducted by teachers, it was found that there were still many students who had not reached the KKM score, which was as many as 6 people, participants who got the KKM pass score of 16 people, and for students whose scores passed KKM only 9 people. In order to achieve the goals and learning outcomes, teachers must pay attention to teaching modules that have been designed and can be applied to the implementation of the learning process regarding the sarunai pupuik musical instrument.